Plant-related quality attributes affecting FcγRIIIa binding: affinity chromatography analysis of rituximab glycovariants from Nicotiana benthamiana - Tengattini, Sara; Tini, Aurora; Marusic, Carla; Rinaldi, Francesca; Senini, Isabella; Calleri, Enrica; Perez, Virginia; Pisano, Claudio; Donini, Marcello; Temporini, Caterina (Frontiers in Plant Science, 2025)
Monoclonal antibodies (mAb) produced in plants, known as plantibodies, represent a cost-effective alternative to conventional mammalian cell cultures. Glycoengineering processes are needed to alter N-glycosylation, avoiding plant-typical glycans and enabling, for anti-cancer mAbs, the production of biobetters with improved antibody-dependent cell-mediated cytotoxicity (ADCC). In this study, glycovariants of the mouse/human chimeric anti-CD20 antibody rituximab were produced in Nicotiana benthamiana plants by transient expression using vacuum-agroinfiltration technology and LED lighting. To modify the glycosylation profile, treatment with kifunensine mannosidase I inhibitor (K) was used as well as ΔXF N. benthamiana plants optimized by “genome editing”. The produced plantibodies were characterized to assess their structural properties, including primary sequence and glycosylation profile. Binding to the FcγRIIIa receptor was investigated by affinity chromatography to explore plantibody ADCC. The influence of the glycosylation on FcγRIIIa receptor affinity was evaluated as well as the impact of post-translational modifications (PTMs). Both glycoengineering strategies were shown to produce mAbs with comparable or improved affinity for FcγRIIIa receptor. For the first time, different in vivo glycoengineering approaches have been compared through the characterization of the resulting mAbs and their affinity for FcγRIIIa receptor. This insight into the correlation among the expression system, plantibody glycoprofile, and predicted ADCC of individual glycoforms has not been previously reported and provides valuable support for the development of plant-based biosimilars.